PEREMPUAN DAN PERKOSAAN MEI 1998 DALAM DUA CERPEN KARYA SENO GUMIRA AJIDARMA: KRITIK SASTRA FEMINIS - Maretta Dwi Anjani; Y. Yulianeta; H. Halimah (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
The May 1998 rape is one of the historic events that has yet to be resolved. This event is portrayed in literary works as a sociocultural document. Seno Gumira Ajidarma as the author and journalist describes the incident through his short stories, namely "Clara" (1998) and "Jakarta, 14 February 2039" (1999). The short story about the rape in May 1998 is full of women's issues and gender injustice in society. This study seeks to uncover how female characters and the rape in May 1998 are depicted in short stories using a radical feminist literary criticism. Descriptive-qualitative method is used in this research. The results of the analysis show that the May 1998 rapes show a gender imequality, because women are seen as parties who have the right to be controlled by men. Even in the act of rape, women are only seen as an object. Because of the rape, female characters, both victims of violence and children born from rape, have to bear the severe trauma. This is in accordance with the radical feminist view that rape is the basis for men to practice their power and control over women, and the demand that women must regain control over their body autonomy.